PERANAN KEMAJUAN TEKNOLOGI TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI DKI JAKARTA DAN IMPLIKASI KEBIJAKANNYA - askinatin, mien (Badan Pengkajian dan Penerapan Teknologi, 2011)
Total Factor Productivity Growth (TFPG) is an approach to determine the role of technology progress on economic growth. The calculation of TFPG in this study is use the accounting growth method. Based on data in 1984-2007, TFPG of DKI Jakarta seen coincides with TFPG of Indonesia graphically. This is reinforced by the correlation coefficient value of 87.03 between them. DKI Jakarta provincial economy largely sustained by capital stock which is supported by the growth of TFP. For an accelerated economic growth throughsupport for a strong technology growth, required an atmosphere of economic, social and political stability in an effort to avoid a crisis as happened in 1998.